Focus group interview as a data gathering tool: Its application to nurses' understanding of HIV infection and AIDS - N. J. Chamane; W. Kortenbout (AOSIS, 1996)
The focus group interview (FCI) is a research method not commonly used by nurses. It is an effective method if qualitative data are needed and may be used independently to get indepth information, but also can be used in conjunction with tools such as questionnaires, to elicit information that could not be gathered otherwise. For the FGI to be applied correctly the researcher must be well versed with its contents, and ensure that the primary reason for using such a method is solely to collect data. Other reasons like decision-making or reaching a consensus would not be appropriate.